Adaptasi Alat Ukur Skala Kemandirian Pembelajaran Elektronik Pada Mahasiswa di Indonesia - Amalia, Meidina; Susanto, Hery (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
The aim of this study was to evaluate the psychometric properties and feasibility of the e-Learning Autonomy Scale (e-LAS) when adapted for use in an Indonesian context, specifically focusing on students involved in electronic-based learning. This study used convenience sampling technique with a total sample of 188 participants who are students in Indonesian higher education and participate in e-learning. The data analysis performed was reliability testing using the SPSS programme and validity testing with CFA using JASP software. The reliability test, conducted using Cronbach's alpha, produced a result of 0.789, deemed acceptable by DeVellis (1991) criteria. To establish validity evidence for the adapted e-LAS measuring instrument, a multifacete approach was undertaken by the researchers. This involved gathering evidence through expert review, cognitive interviews, confirmatory factor analysis, and convergent analysis. The findings indicate that the adapted Indonesian version of the e-LAS exhibits acceptable reliability and is supported by strong validity evidence, affirming its effectiveness in measuring learning autonomy among students engaged in electronic-based learning in the Indonesian context.